Utilising the effect of reaction concentration to tune the physical properties of hyperbranched polymers synthesised using transfer-dominated branching radical telomerisation (TBRT). Issue 16 (21st March 2023) - Cassin, Savannah R.; Wright, Stephen; Mckeating, Samuel; Penrhyn-Lowe, Oliver B.; Flynn, Sean; Lomas, Sarah; Chambon, Pierre; Rannard, Steve P.
Abstract : TBRT allows the control of cyclisation within branched polymer architectures by simply changing dilution. Increased cyclisation leads to changes in physical properties, therefore, tunig of behaviour is available without changing starting materials. Abstract : The formation of complex polymer architectures with novel physicochemical properties is of great importance in the development of next generation advanced materials. The recent reports of Transfer-dominated Branching Radical Telomerisation (TBRT) provide readily accessible routes to a range of previously inaccessible macromolecular architectures, utilising free radical reactions under telomerisation conditions. Herein, we describe the variation in the physical properties of hyperbranched polymers synthesised via TBRT, upon the manipulation of the reaction concentration at which the telomerisations were conducted. Through the careful control of multi-vinyl taxogen to telogen ratios, we have shown that the formation of a crosslinked network can be prevented at various reaction concentrations (0 wt% (bulk) – 90 wt% solvent), leading to materials with tuneable physical properties. The impact of excess solvent (≥70 wt% solvent) was exemplified by the significant variation of glass transition temperatures of the resulting materials and the reduction of telogen incorporated in the final structure, providing clear evidence of intramolecular cyclisation.